Volodymyr Sosiura as the creator of the of socialist realism canons: to the ideological and aesthetic principles of writer’s creativity (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
In the article it is studied the pecularities of Sosiura's artistic world of nineteen twenties – nineteen forties, their main ideaological and theme – based, artistic and aesthetic achievements, when the author was in the epicenter of literary process in USSR and the forefront of creation of the main ideologem, stylistic and aesthetic features of social realizm. Aspiring to be in a new social reality, V. Sosiura was formed as an artist of compromise plan, he was afraid to take steadfast literal position, constantly manoeuvring between creative work and the system of ideaological pressure from totalitarian authority. It is analyzed Sosiura's work of nineteen – twenties – the poem "To Neoclassics" – it is studied the essence of ideaological denunciation in it and general position of the poet, due to this position he wanted to confirm his loyalty to communist party.
Keywords: national character; revolutional neoromantism; modernizm; social realizm; creative process